Impact of Job Stress, Work Engagement, Job Satisfaction, and Organizational Commitment on Job Burnout: A Study of Academicians in Private Universities - Malik, Azam (International Review of Management and Marketing, 2025)
Burnout is not just an individual issue but also has significant impacts on both individuals and organizations. Exhausted and overwhelmed teachers are less effective in their teaching practices, leading to decreased student achievement and academic outcomes. Moreover, burnout can negatively impact teacher retention rates, leading to a loss of experienced and talented educators in the profession. The purpose of this study is to investigate the relationship and impact of job stress, work engagement, job satisfaction, and organizational commitment and job burnout among the faculty members in private educational institutions in India. A structured questionnaire was used to gather primary data from 171 teaching staff members from different private educational institutions in India. Means, Correlations and Regression are used in the statistical procedures were among the many tools and methods used in data analysis. The findings demonstrated a strong relationship between burnout and workplace stress as well as between job satisfaction, work engagement, and job stress. Furthermore, significant relationships between burnout and job satisfaction were found. These results demonstrate how important these factors are in predicting burnout and commitment to work. In order to ensure the provision of high-quality services inside educational institutions, this study highlights the necessity for management strategies to give the evaluation of both physical and mental working conditions top priority. In educational contexts, employee happiness plays a crucial role in fostering organizational engagement and reducing job burnout.